2018
DOI: 10.1186/s13104-018-3157-4
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in mucopolysaccharidoses: construction of a specific measure using the focus group technique

Abstract: ObjectiveTo describe the perceptions of patients, their caregivers, and their healthcare providers to the development of a new specific instrument for assessment of the quality of life (QoL) in patients with mucopolysaccharidoses (MPS) using a qualitative focus group (FG) design. FGs were held in two Brazilian states (Rio Grande do Sul and Rio de Janeiro).ResultsThree versions of the new instrument were developed, each for a different age group: children (age 8–12 years), adolescents (age 13–17), and adults (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…While studies have shown that the quality of life of patients with MPS diseases and their caregivers is negatively impacted, there is a lack of specific measures for this patient population [32, 33]. The impact of MPS diseases on the family has been shown to be similar to that for other paediatric outpatients with chronic illnesses and caregiver burden increases with disease progression and loss of mobility [32].…”
Section: Discussionmentioning
confidence: 99%
“…While studies have shown that the quality of life of patients with MPS diseases and their caregivers is negatively impacted, there is a lack of specific measures for this patient population [32, 33]. The impact of MPS diseases on the family has been shown to be similar to that for other paediatric outpatients with chronic illnesses and caregiver burden increases with disease progression and loss of mobility [32].…”
Section: Discussionmentioning
confidence: 99%
“…Data were obtained via caregiver focus groups, video recordings of affected boys in an unstructured play setting, individual caregiver interviews either in person or by phone, medical record review, a meeting of representatives from patient advocacy groups and international experts, individual expert consultation, and literature review [28]. The focus group approach was selected for obtaining caregiver data because it has been used to understand the subjective experience of individuals and families in the MPS community, most recently for understanding quality of life, caregiver burden, and patient-reported outcomes [[29], [30], [31]]. Literature review of PubMed and Google Scholar involved the search terms mucopolysaccharidosis, “Hunter syndrome,” behavior, and “cognitive decline.” Experts were selected for consultation based on publications and/or international presentations on Hunter syndrome, or a history of advisory board work on Hunter syndrome.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, stakeholders such as industry, regulators, and payers have become increasingly interested in obtaining insight from patient/caregiver throughout the drug development lifecycle [ 37 ]. Moreover, there is a scarcity of studies and appropriate instruments for determining the QoL in patients with MPS [ 38 ]. Apart from this, several national strategies across Europe encourage involving patients and their families in research and incorporating their voices into the policy-making for rare diseases [ 17 ].…”
Section: Discussionmentioning
confidence: 99%